Nephropathy is aggravated by fatty acids in diabetic kidney disease through tubular epithelial cell necroptosis and is alleviated by an RIPK-1 inhibitor - Qi Yu; Ying Chen; Youlu Zhao; Shuo Huang; Xiaohong Xin; Lei Jiang; Hui Wang; Wenyan Wu; Lei Qu; Chengang Xiang; Suxia Wang; Gang Liu; et al. (Karger Publishers, 2023)
Introduction: Diabetic kidney disease (DKD), one of the leading causes of end-stage renal disease, has complex pathogenic mechanisms and few effective clinical therapies. DKD progression is accompanied by the loss of renal resident cells, followed by chronic inflammation and extracellular matrix deposition. Necroptosis is a newly discovered form of regulated cell death and is a major form of intrinsic cell loss in certain diabetic complications such as cardiomyopathy, intestinal disease, and retinal neuropathy; however, its significance in DKD is largely unknown. Methods: In this study, the expression of necroptosis marker phosphorylated MLKL (p-MLKL) in renal biopsy tissues of patients with DKD was detected using immunofluorescence and semiquantified using immunohistochemistry. The effects of different disease-causing factors on necroptosis activation in human HK-2 cells were evaluated using immunofluorescence and western blotting. db/db diabetic mice were fed a high-fat diet to establish an animal model of DKD with significant renal tubule damage. Mice were treated with RIPK1 inhibitor RIPA-56 to evaluate its renal protective effects. mRNA transcriptome sequencing was used to explore the changes in signaling pathways after RIPA-56 treatment. Oil red O staining and electron macroscopy were used to observe lipid droplet accumulation in renal biopsy tissues and mouse kidney tissues. Results: Immunostaining of phosphorylated RIPK1/RIPK3/MLKL verified the occurrence of necroptosis in renal tubular epithelial cells (RTECs) of patients with DKD. The level of the necroptosis marker p-MLKL correlated positively with the severity of renal functional, pathological damages, and lipid droplet accumulation in patients with DKD. High glucose and fatty acids were the main factors causing necroptosis in human renal tubular HK-2 cells. Renal function deterioration and renal pathological injury were accelerated, and the necroptosis pathway was activated in db/db mice fed a high-fat diet. Application of RIPA-56 effectively reduced the degree of renal injury, inhibited the necroptosis pathway activation, and reduced necroinflammation and lipid droplet accumulation in the renal tissues of db/db mice fed a high-fat diet. Conclusion: The present study revealed the role of necroptosis in the progression of DKD and might provide a new therapeutic target for the treatment of DKD.